Perkawinan Anak Antara Legalitas Formal dan Realitas Sosial di Masyarakat - Tabi, Sunarti; Moonti, Roy Marthen; Ahmad, Ibrahim (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Child marriage in Indonesia is still a serious problem despite regulations that limit the minimum age of marriage. The revision of Law No. 16/2019 sets the minimum age at 19 years, but the practice of marriage dispensation has actually increased. This phenomenon reflects the gap between formal legality and social reality which is influenced by factors such as low education, patriarchal culture, conservative religious interpretations, social pressure, and poverty. Dispensation for marriage is often granted without an in-depth assessment of the child's readiness, ignoring the principle of the best interests of the child. Law enforcement has not been effective due to the lack of legal literacy, weak supervision, and the dominance of local values. Prevention efforts require an interdisciplinary approach through reproductive health education, strengthening social protection, community participation, and synergy between institutions. Therefore, the elimination of child marriage must be a strategic policy based on the transformation of social norms and the protection of children's rights in a holistic and sustainable manner within the framework of gender perspective development and social justice.